Transcription factors involved in the regulation of natural killer cell development and function: an update - Luevano, Martha E.; Madrigal, Alejandro; Saudemont, Aurore (Frontiers in Immunology, 2012)
Natural Killer (NK) cells belong to the innate immune system and are key effectors in the immune response against cancer and infection. Recent studies have contributed to the knowledge of events controlling NK cell fate. The use of knockout mice has enabled the discovery of key transcription factors (TFs) essential for NK cell development and function. Yet, unwrapping the downstream targets of these TFs and their influence on NK cells remains a challenge. In this review we discuss the latest TFs described to be involved in the regulation of NK cell development and maturation.